2021
DOI: 10.2147/jpr.s293119
|View full text |Cite
|
Sign up to set email alerts
|

Race Differences in Resilience Among Older Adults with Chronic Low Back Pain

Abstract: Introduction Racial minorities are disproportionally affected by pain. Compared to non-Hispanic Whites (NHWs), non-Hispanic Blacks (NHBs) report higher pain intensity, greater pain-related disability, and higher levels of mood disturbance. While risk factors contribute to these disparities, little is known regarding how sources of resilience influence these differences, despite the growing body of research supporting the protective role of resilience in pain and disability among older adults with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 79 publications
0
8
0
Order By: Relevance
“…In a retrospective study, Morrison et al (2021) found that Black and Hispanic residents were less likely to have pain behaviors documented or to receive analgesics than NHW residents. Morais et al (2021) found that higher levels of gratitude and trait resilience were protective against movement-evoked pain among NHW participants; however, gratitude was associated with lower functional performance in Black participants.…”
Section: Resultsmentioning
confidence: 85%
“…In a retrospective study, Morrison et al (2021) found that Black and Hispanic residents were less likely to have pain behaviors documented or to receive analgesics than NHW residents. Morais et al (2021) found that higher levels of gratitude and trait resilience were protective against movement-evoked pain among NHW participants; however, gratitude was associated with lower functional performance in Black participants.…”
Section: Resultsmentioning
confidence: 85%
“…Four papers [ 18 , 42 , 44 , 45 ] provided socioeconomic demographics with the majority of participants reporting low socioeconomic status. Pooled data of 170 participants across three studies demonstrates that most participants (35.9%) had an annual income of <US $20,000.…”
Section: Resultsmentioning
confidence: 99%
“…The Roland-Morris Disability Questionnaire (RMDQ) (n = 5) and the Short Physical Performance Battery (SPPB) (n = 4) were the most common assessments tools used. The SPPB was used across a range of musculoskeletal conditions including back pain [ 44 ], knee osteoarthritis [ 18 ] and after hip fracture [ 41 ], whilst the RMDQ was used for participants with back pain [ 43 , 46 , 47 , 49 , 50 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has been historically focused on vulnerability and risk factors (e.g., negative mood, pain catastrophizing, fear avoidance) influencing pain and functioning. This represents a significant knowledge gap as emerging literature suggests that individuals with chronic pain have the ability to exhibit resilience [ 9 14 ]. Conceptualized as a dynamic construct, resilience is defined as a process of adapting to adversity, threats, or significant sources of stress [ 15 ].…”
Section: Introductionmentioning
confidence: 99%